How to stay safe while extending the mind. - Hirvelä, Jaakko (Synthese, 2020)
According to the extended mind thesis, cognitive processes are not confined to the nervous system but can extend beyond skin and skull to notebooks, iPhones, computers and such. The extended mind thesis is a metaphysical thesis about the material basis of our cognition. As such, whether the thesis is true can have implications for epistemological issues. Carter has recently argued that safety-based theories of knowledge are in tension with the extended mind hypothesis, since the safety condition implies that there is an epistemic difference between subjects who form their beliefs via their biological capacities and between subjects who have extended their cognition. Kelp, on the other hand, has argued that a safety-based theory of knowledge can be correct only if the extended mind thesis is true. While these claims are not logically inconsistent, they do leave the safety theorist in an uncomfortable position. I will argue that safety-based theories of knowledge are not hostage to the truth of the extended mind thesis, and that once the safety condition is properly understood it is not in tension with the extended mind thesis.